Comparative Assessment Of Insulin Sensitivity And Pancreatic Beta Cell Function In Diabetics And Non-Diabetics - ATRINANDAN P USGAONKAR; CHITRA Y. DHUME; SUNANDA D. AMONKAR (International Journal of Pharma and Bio Sciences, 2012)
The study was carried out to evaluate and compare insulin resistance, pancreatic beta cell dysfunction and lipid profile in non-diabetic first degree relatives of type 2 diabetics and also to evaluate the same parameters in diabetics with varying duration. 190 subjects were taken and categorized based on duration of diabetes. Fasting blood sugar (F.B.S.L.), Post prandial blood sugar (P.P.B.S.L.), Glycated haemoglobin (HbA1c), plasma insulin, insulin resistance, beta cell dysfunction and lipid profile was estimated. Results showed a significant difference in insulin resistance and no significant difference in beta cell dysfunction in non-diabetic first degree relatives. Insulin resistance was found to increase and beta cell function decrease significantly. No significant difference was observed between Low density and High density lipoprotein cholesterol levels between first degree relatives and controls while other lipid parameters showed a significant change. A good correlation was observed of insulin with insulin resistance, FBSL and HbA1c.